Analisis Kesulitan Belajar Mahasiswa dalam Memahami Konsep Mekanika pada Pembelajaran Fisika Dasar - Riris Idiawati; Ferdiana Ferdiana; Aminatur Rosyidah; Ulfiyatul Fitriyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to identify various aspects that pose obstacles or difficulties for students in learning Mechanics. This study uses a qualitative descriptive approach that focuses on describing the types of difficulties students encounter in solving mechanics problems. The research subjects were first-semester students of the Science Education Study Program at KH. Mukhtar Syafaat University (UIMSYA) Blokagung Banyuwangi who were taking Basic Physics courses on Mechanics material. Data collection was carried out through diagnostic tests and interviews with students. The instruments used were diagnostic tests and interview guidelines. The location of students' learning difficultdiies was analyzed based on the errors that appeared in the completion of the diagnostic test. The results showed that the main difficulty students had in learning mechanics was in mastering basic mathematical skills, particularly in differential and integral material. Therefore, lecturers or teachers need to design and develop more appropriate learning strategies so that students' problem-solving skills can improve.